Geoparks — Potential for Outdoor Learning of Subjects Geography and Biology - Nevřelová, Marta; Ružek, Ivan (Scientia in educatione, 2017)
The first initiatives seeking to establish geoparks in Slovakia date back to the years 1998–2000, when ideas for the establishment and management of these areas began to emerge in Banská Štiavnica and later also in Banská Bystrica and Fiľakovo. Since then, four geoparks have been established in Slovakia (Banská Bystrica geopark, Banská Štiavnica geopark, Novohrad – Nógrád geopark and Sandberg-Pajštún geopark). Geoparks have considerable potential as sites for outdoor learning, especially learning through field trips. Teachers can also use these areas for project learning. It is therefore very important that information and ideas about the possibilities of outdoor learning are available to the general public. This paper seeks to evaluate the potential of Slovak geoparks for outdoor learning. For this purpose, the method chosen was based on a review of geopark sites and possibilities how to use them for outdoor learning in compliance with syllabi outlined in geography and biology textbooks. The results of our review indicate that the geoparks have significant potential for outdoor learning, especially in relation to a part of 9th grade primary school Geography syllabus which focuses on Slovakia. This also pertains to 4th grade Biology taught in 8-year grammar schools and 8th grade Biology in primary schools, which subsumes geology and ecology, possibly also for 3rd graders in 8-year grammar schools.